Keharmonisan Keluarga dan Manajemen Konflik Perempuan Legislator DPRD Sumatera Barat dalam Perspektif Islam - Hafizul Furqan (Journal of Innovative and Creativity, 2025)
Women’s involvement in Indonesian politics has grown considerably, yet this progress also brings challenges in the form of a double burden that can affect family harmony. This study seeks to explore the types of conflicts experienced within the families of female legislative members in the Regional House of Representatives (DPRD) of West Sumatra Province, analyze the conflict management strategies they employ, and examine efforts to foster household harmony through the lens of Islamic law. The research adopts a qualitative approach with a field research design. Primary data were obtained through interviews with four female legislators, while secondary data were gathered from relevant literature. The findings indicate that conflicts often take the form of differences in opinion, emotional outbursts, debates, as well as disagreements in parenting and work management. The resolution strategies applied include choosing silence, restraining from verbal retaliation, yielding, and making adjustments. The study concludes that family harmony can be maintained through mutual support and understanding between spouses, in line with the Islamic principles of sakinah, mawaddah, and rahmah. These findings not only enrich the body of literature on Islamic family law but also provide practical recommendations for policies that support female legislators.